1995
DOI: 10.1126/science.7542403
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Binding and Presentation by Mouse CD1

Abstract: CD1 molecules are distantly related to the major histocompatibility complex (MHC) class I proteins. They are of unknown function. Screening random peptide phage display libraries with soluble empty mouse CD1 (mCD1) identified a peptide binding motif. It consists of three anchor positions occupied by aromatic or bulky hydrophobic amino acids. Equilibrium binding studies demonstrated that mCD1 binds peptides containing the appropriate motif with relatively high affinity. However, in contrast to classical MHC cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
128
0
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 239 publications
(132 citation statements)
references
References 28 publications
3
128
0
1
Order By: Relevance
“…Although CD4 ϩ and DN NKT populations may harbor shared TCR specificities, there may be important differences between the two cell types. In normal mice, we have demonstrated that DN, but not CD4 ϩ , NKT cells of spleen and liver express inhibitory NK markers of the Ly-49 type, 4 and it has been reported that IL-4 production upon stimulation was found preferentially in the CD4 ϩ subset (Ref. 12 and M. Sköld and S. Cardell, manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although CD4 ϩ and DN NKT populations may harbor shared TCR specificities, there may be important differences between the two cell types. In normal mice, we have demonstrated that DN, but not CD4 ϩ , NKT cells of spleen and liver express inhibitory NK markers of the Ly-49 type, 4 and it has been reported that IL-4 production upon stimulation was found preferentially in the CD4 ϩ subset (Ref. 12 and M. Sköld and S. Cardell, manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
“…The CD1 molecules, unlike conventional MHC molecules, present lipids and glycolipids (1)(2)(3), as well as peptides (4,5), to T lymphocytes. In the mouse, different types of TCR␣␤ ϩ T cells have been described that recognize CD1d in the absence of added Ag (6 -10).…”
mentioning
confidence: 99%
“…The production and purification of soluble recombinant mCD1 from D. melanogaster tissue culture cells were previously described (57). Purified mCD1 protein was incubated for 12 h at room temperature with a 3-fold molar excess of ␣-GalCer.…”
Section: Preparation and Use Of ␣-Galcer Mouse Cd1 Dimersmentioning
confidence: 99%
“…Perhaps reflecting the bias of the times, hydrophobic peptides (selected from random peptide libraries) were initially proposed to associate with CD1d [37] but were never shown to be recognized by iNKT cells.…”
Section: The Elusive Inkt Ligandmentioning
confidence: 99%